Prognostic Value of N-Terminal Prohormone of Brain Natriuretic Peptide (NT-ProBNP) and Killip Score in Patients with Acute Decompensated Heart Failure (ADHF) A Sarawak Tertiary Centre Experience - Ling, Hwei Sung; Chung, B.K.; Chua, P.F.; Fong, A.Y.Y. (Elsevier, 2019)
Background: Mortality and readmission due to heart failure is contributing to increase healthcare burden. NT-proBNP is known for its role in diagnosis of heart failure. Higher Killip score was found to be associated with more inpatient death among ADHF patients in Sarawak General Hospital. There are limited data on usage of NT proBNP and Killip score to prognosticate post discharge clinical outcome. Objective: We aim to explore association of admission NT-ProBNP and Killip score with 90-day mortality and readmission outcome. Materials & Methods: 68 patients with a primary diagnosis of ADHF were recruited between December 2017 to October 2018 in Sarawak General Hospital. NT-proBNP samples were collected within 24hours from diagnosis. Patients were prospectively follow up for 90 days from discharge. ROC curve analysis was applied to determine the cut-off value of NT-proBNP with optimal sensitivity and specificity. Factors (Age, gender, hypertension, diabetes, dyslipidemia, admission BP, heart rate and EF) were investigated for their role in affecting the discriminative value of NT-proBNP. Chisquare analysis was used to compare differences in outcomes between patients with NT-proBNP readings N5055pg/ml and those with higher Killip score. Results: Patients recruited had a median age of 63+/-17years old and 57% are male. 36(54%) patients had admission Killip score of N2. 16 (28%) patients recorded cumulative event of death and readmission in 90 days post discharge. The median value of NTproBNP recorded in the cohort was 4115 pg/ml. ROC analysis identified NT-proBNP as a useful tool in determining 90-day clinical outcome (AUC=0.694, p=0.024). At the level of 5055 pg/ml, NTproBNP had a sensitivity and specificity of 66% and 69%. Performance of NT-proBNP significantly improved in subpopulation of patients who are less than 65 years old, male gender and those with admission systolic blood pressure N100mmHg respectively (AUC up to 0.871, p= 0.004). A combination of Killip score N2 with NTproBNP N5055 pg/ml showed almost 5-fold increase in risk of developing 90-day event (OR 4.5714, 95% CI 1.3-15.7, p=0.0158). Conclusion: Objective assessment using NT-proBNP and clinical parameter of Killip scoring during admission are potentially useful in determining 90-day outcome in patients with ADHF